Determining the optimal threonine:lysine ratio in starter diets for the segregated early-weaned pig - J R Bergstrom; W B Nessmith Jr; C A Civis; Jim L Nelssen; Michael D Tokach; Robert D Goodband (Kansas Agricultural Experiment Station Research Reports, 1996)
A 14-day growth trial was conducted to determine the threonine: lysine ratio necessary to optimize growth performance of the segregated early-weaned (SEW) pig. Twelve experimental diets included two levels of lysine (1.15% and 1.5% apparent digestible lysine) and six apparent digestible threonine: lysine ratios (40, 45, 50, 55, 60, and 65 %) in a 2 x 6 factorial arrangement. Growth performance was improved by feeding 1.5% rather than 1.15% digestible lysine. Growth performance decreased linearly as the digestible threonine: lysine ratio increased. Although a significant quadratic response was not observed, this reduction in growth performance did not appear to occur until the threonine ratio exceeded 45% of lysine on an apparent digestible basis. These data indicate that the threonine requirement for the SEW pig is approximately 45% of digestible lysine.; Swine Day, Manhattan, KS, November 21, 1996
Keywords: Swine day; 1996; Kansas Agricultural Experiment Station contribution; no. 97-142-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 772; Swine; Early-weaned pigs; Amino acids; Threonine